The clinical diagnostic value of plasma miR-592 and miR-217-3p levels in retinoblastoma - Luo, JinYan; Huang, BinLin; Hu, QiYu; Li, RuJie; Chen, Jun; Yuan, LingMei; Peng, Yuan (Journal of Medical Biochemistry, 2022)
Background: This study was designed to investigate the abnormal expression of plasma miR-592 and miR-217-3p in retinoblastoma (Rb) and explore the clinical diagnostic value of their expression levels for Rb. Methods: The 100 Rb patients who came to Nanchang Hongdu Hospital of Traditional Chinese Medicine from January 2018 to January 2019 were selected as the Rb group, and 100 healthy patients who came to the physical examination centre during the same period were selected as the control group. Real-time fluorescence quantitative PCR (qRT-PCR) was used to detect the expression levels of plasma miR-592 and miR-217-3p in all subjects; analyse the relationship between plasma miR-592 and miR-217-3p levels and the clinicopathological characteristics of Rb. Pearson correlation analysis evaluated the relationship between plasma miR-592 and miR-217-3p levels and overall survival. Results: Plasma levels of miR-592 and miR-217-3p in the Rb group were significantly higher than those in the control group (p<0.0001), and the expression of miR-592 was significantly correlated with family genetic history (p 0.0001), tumour bias (p=0.0081), lymph node metastasis (p=0.0048) and pathological grade (p=0.0025), and the expression of miR-217-3p was significantly related to family genetic history (p 0.0001), optic nerve infiltration (p 0.0001), lymph node metastasis (p=0.0090), and pathological grade (p 0.0001). The high expression of miR-592 and miR-217-3p presents a more serious pathological manifestation of Rb, and the overall survival of patients is significantly shortened with the increase of miR-592 (r=0.2276, p=0.0052) and miR-217-3p levels (r=-0.6461, p 0.0001). Conclusions: and miR-217-3p are highly expressed in the plasma of Rb patients, and their elevated levels present severe pathological manifestations of Rb and shortened overall survival, which is expected to become biomarkers for clinical diagnosis of Rb.